1999
DOI: 10.1177/000348949910800408
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Comparative Trial of Ciprofloxacin versus Clarithromycin in the Treatment of Acute Bacterial Sinusitis

Abstract: This multicenter, randomized, double-blind trial compared the efficacy and safety of ciprofloxacin (CIP; 500 mg twice daily for 10 days, placebo for 4 days) to those of clarithromycin (CLARI; 500 mg twice daily for 14 days) in 560 adults with clinically documented and radiologically confirmed acute sinusitis. Of 457 efficacy-valid adults (236 CIP, 221 CLARI), clinical resolution plus improvement at the end of therapy was 84% for CIP-treated patients compared to 91% of CLARI recipients (CI95 = -0.131, -0.013). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…The 88.6% clinical success rate visit achieved with telithromycin at the TOC in this study is similar to that seen in previous studies with telithromycin [31][32][33][34] and comparable with rates of clinical success observed for other antibacterials in similarly designed ABS clinical trials [9][10][11][12][13][14][15] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The 88.6% clinical success rate visit achieved with telithromycin at the TOC in this study is similar to that seen in previous studies with telithromycin [31][32][33][34] and comparable with rates of clinical success observed for other antibacterials in similarly designed ABS clinical trials [9][10][11][12][13][14][15] .…”
Section: Discussionsupporting
confidence: 89%
“…Antibacterial therapy should therefore provide coverage of these organisms. The most commonly prescribed antibacterials are -lactams, second-and third-generation cephalosporins, and macrolides 5,6 ; numerous clinical trials involving adult patients with ABS have demonstrated clinical efficacy rates for these agents ranging from 82 to 98% [9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Recently, however, the choice of antibacterial therapy for ABS has become complicated by increased bacterial resistance -in particular, among S. pneumoniae [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…No major side effects were otherwise observed. of antibiotics had an efficacy ranging from 50-88% (19,24,32,(34)(35)(36)(37)(38)(39) , as compared to an efficacy of 14-91% (19,24,32,(34)(35)(36)(37)(38)(39) for placebos compared in the studies. A similar comparison of the side effects showed that 2.7-59% (1,9,24,(35)(36)(37)(38)(39) of patients on antibiotics reported side effects, while 0-40.7% (19,24,(35)(36)(37)(38)(39) of patients on placebos showed adverse effects.…”
Section: Levofloxacin (Figure 4)mentioning
confidence: 94%
“…Les examens bactériologiques sont rarement effectués en routine. En revanche, ils font partie des protocoles d'études réalisées pour l'évaluation des antibiotiques [188][189][190]. Dans presque toutes les études françaises, le recueil des sécrétions est fait par voie endonasale au méat moyen [191,192].…”
Section: Examens Bactériologiquesunclassified